2020
DOI: 10.1111/tmi.13338
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards female genital cutting among adolescents in rural Burkina Faso: a multilevel analysis

Abstract: objective Despite decades of abandonment efforts, female genital cutting (FGC) prevalence rates in Burkina Faso remain high. We present updated prevalence data from rural adolescents and examine factors associated with FGC receipt and attitudes, testing predictions of social convention and modernisation theory regarding the abandonment process.methods We interviewed 1644 adolescents aged 12-20 years from 10 villages and one sector of Nouna town in the Nouna Health and Demographic Surveillance site in late 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…In this study, we found that the practice of FGC has declined consistently over the years. There is evidence that the younger cohort of women exhibited a reduction in the level of FCG practice compared to older cohorts This finding was in agreement with the outcomes of similar studies conducted in some parts of sub-Saharan Africa and other parts of the world [21,[34][35][36]. Our findings point to the importance of public health campaigns against FGC in Nigeria.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that the practice of FGC has declined consistently over the years. There is evidence that the younger cohort of women exhibited a reduction in the level of FCG practice compared to older cohorts This finding was in agreement with the outcomes of similar studies conducted in some parts of sub-Saharan Africa and other parts of the world [21,[34][35][36]. Our findings point to the importance of public health campaigns against FGC in Nigeria.…”
Section: Discussionsupporting
confidence: 91%
“…17 18 Eight studies had overlapping age groups where the authors did not segregate results between women and girls. These studies were categorised into the most appropriate category as either women [19][20][21] (table 1) or girls [22][23][24][25][26] (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Two previous ARISE surveys have been conducted in Nouna. [34][35][36][37] Established in 1992, the Nouna HDSS includes the town of Nouna and surrounding villages. 38 Composed primarily of rural areas, the HDSS includes approximately 124,960 inhabitants and is distributed over 1,775 km 2 .…”
Section: Methodsmentioning
confidence: 99%